PENGARUH KUALITAS PRODUK DAN LAYANAN PURNA JUAL TERHADAP KEPUASAN PELANGGAN PENGGUNA SMARTPHONE MEREK XIAOMI DI FAKULTAS EKONOMI UNIVERSITAS KRISNADWIPAYANA - Wirdianto Abdul Jabar; Imam Wibowo; Nino Nopriandi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This research aims to know influence of product quality and after sales service on customer satisfaction using Xiaomi smartphones. The population and sample of this study were students of the economics faculty of the Krisnadwipayana University class of 2017 with a total of 58 students. Research analysis method using simple regression analysis technique and simultaneous regression analysis. The hypothesis test using the F test and t test. The results of the study state that partially, product quality and after-sales service have a positive and significant effect on consumer satisfaction. Simultaneously, product quality and after-sales service have a positive and significant effect on consumer satisfaction.